2002
DOI: 10.2136/sssaj2002.0284
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Diet Phosphorus Effects on Phosphorus Losses in Runoff from Land-Applied Manure

Abstract: Phosphorus (P) losses from land-applied manure can contribute to nonpoint source pollution of surface waters. Dietary P levels influence P concentrations in animal manures and may affect P losses from land-applied manure. The objective of this study was to determine the effects of dairy diet P concentration on P losses in runoff from landapplied manure. Manures with P concentrations of 0.48 and 1.28 % P from two dietary P levels were applied to a silt loam soil 25 wet ton/a (36 and 96 lb P/a, respectively). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 6 publications
4
52
2
1
Order By: Relevance
“…Additionally, the mobility of P in cattle manures may have increased because of an increase in the P content of winter feed of cattle caused by a switch from hay to silage and the inclusion of high P concentrate feeds. Enhanced dietary P increases the proportion of TP in manure that is soluble or colloidal, and these P fractions have a greater vulnerability to runoff loss in comparison with PP (Ebeling et al 2002). Quantitative information on these changes is limited, leaving the mobility of manure P and vulnerability to loss an unresolved issue to be addressed in interpreting eutrophication history and the identifying control and remedial measures.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the mobility of P in cattle manures may have increased because of an increase in the P content of winter feed of cattle caused by a switch from hay to silage and the inclusion of high P concentrate feeds. Enhanced dietary P increases the proportion of TP in manure that is soluble or colloidal, and these P fractions have a greater vulnerability to runoff loss in comparison with PP (Ebeling et al 2002). Quantitative information on these changes is limited, leaving the mobility of manure P and vulnerability to loss an unresolved issue to be addressed in interpreting eutrophication history and the identifying control and remedial measures.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, reducing the P content of dairy cow rations to the extent adopted within the current experiment has the potential to have a significant impact on farm P balances, and thus the likelihood of P loss to the environment. In addition, Dou et al (2002) observed an increased proportion of water soluble P in the faeces of cows offered high P diets, while Ebeling et al (2002) showed that P runoff from slurry produced from cows offered a high P diet was considerably greater than for slurry produced by cows offered a low P diet.…”
Section: Cow Fertilitymentioning
confidence: 99%
“…Many studies have shown that dairy cows are often fed more P than they require according to current recommendations (Wu et al, 2001;Valk et al, 2002;Knowlton et al, 2004;Nennich and Harrison, 2008). Manure from dairy cows fed high levels of P has been shown to increase the potential for P runoff losses (Ebeling et al, 2002). Dealing with P losses from livestock production is becoming increasingly important as farms grow larger in number of animals and the P load thereby is becoming concentrated to these spots.…”
Section: Introductionmentioning
confidence: 99%